Guidelines for diseases of the respiratory tract - Płusa, Tadeusz (Przewodnik Lekarza/Guide for GPs, 2007)
The epidemiology of respiratory tract infections and bacterial resistance to antibiotics has been evaluated in clinical trials and creates a basis for empiric antibiotic therapy. Systemic inflammatory response syndrome, septic shock and multiple organ dysfunction syndrome indicate a new target for emergency in pneumonology. In new guidelines for bronchial asthma treatment a ciclesonid and anti-IgE therapy, and tiotropium for chronic obstructive pulmonary disease, have been implemented. Obtained clinical results have confirmed the usefulness of these new therapies. Endobronchial ultrasound and electromagnetic navigation in lung tumours give us new possibilities for diagnostic procedures. On the other hand an increase in telomerase activity in specimens from biopsies of lung tumours is a factor helpful in determining the possibilities of surgical treatment.